Specificity of Translating Icononyms into Diverse Structural Languages (English, French, and Tatar) - N. S. Andrianova; E. N. Bulina; R. R. Mingazova (Научный диалог, 2024)
This study examines proper names functioning as titles of iconographic works (such as ‘Pokrov Bogomateri’ (the Protection of the Mother of God), ‘Voskreseniye Khristovo’ (the Resurrection of Christ), ‘Soshestviye vo ad’ (the Descent into Hell) etc.) in the context of exploring their translation into English, French, and Tatar. A comparative analysis of artionyms (icononyms) is conducted. The sources for this research include catalogs of ancient Russian painting, particularly those from the collection of the State Museum of Fine Arts of the Republic of Tatarstan (Kazan). The paper discusses the challenges involved in translating terms such as ‘umileniye’ (compassion), ‘pokrov’ (protection), and ‘успение’ (dormition) etc. On one hand, doctrinal discrepancies are noted in the target languages, which are attributed to extralinguistic factors (differences in approaches to key Christian doctrines among Orthodoxy, Protestantism, and Catholicism, as well as the absence of cultural elements from the source language in the target language). On the other hand, semantic inconsistencies are identified, which can be explained by attempts at generalization or, conversely, specification of the content of terms aimed at facilitating recipient comprehension. One of the most frequent translational transformations observed is calquing, with identified differences in word formation patterns explained by the distinct typological models of the languages being compared (synthetic, analytic, agglutinative).